2023
DOI: 10.3390/chemengineering7060104
|View full text |Cite
|
Sign up to set email alerts
|

Polycaprolactone Composites/Blends and Their Applications Especially in Water Treatment

Gizem Özge Kayan,
Asgar Kayan

Abstract: Biodegradable poly(ɛ-caprolactone) (PCL) and its composites or blends have received a lot of attention in the last decade because of their potential applications in human life and environmental remediation. Greater efforts have been made to develop biodegradable chemical materials as adsorbents that do not pollute the environment in order to replace traditional materials. Among the numerous types of degradable materials, PCL is currently the most promising, the most popular, and the best material to be develop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 177 publications
0
9
0
Order By: Relevance
“…With the increasing DR of hybrid filaments, the sonic orientation factor of the hybrid filaments increases until reaching its maximum at DR2.8, which is then followed by a gentle changing trend. Meanwhile, the sonic orientation factor contributed by the crystal region and amorphous (including mobile amorphous and rigid amorphous 43,44 ) region also shows a similar changing trend as the sonic orientation factor, reaching their maximum values at DR3.1 and DR2.8, respectively. During this process, segments in the rigid amorphous region will be forced‐oriented quickly, and those in the mobile amorphous region will be hysteresis‐oriented.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…With the increasing DR of hybrid filaments, the sonic orientation factor of the hybrid filaments increases until reaching its maximum at DR2.8, which is then followed by a gentle changing trend. Meanwhile, the sonic orientation factor contributed by the crystal region and amorphous (including mobile amorphous and rigid amorphous 43,44 ) region also shows a similar changing trend as the sonic orientation factor, reaching their maximum values at DR3.1 and DR2.8, respectively. During this process, segments in the rigid amorphous region will be forced‐oriented quickly, and those in the mobile amorphous region will be hysteresis‐oriented.…”
Section: Resultsmentioning
confidence: 75%
“…During this process, segments in the rigid amorphous region will be forced‐oriented quickly, and those in the mobile amorphous region will be hysteresis‐oriented. In addition, it is found that the integral in the crystalline region decreases with the increase in DR, whereas the integral in the amorphous region increases obviously from 42.3 to 53.7, indicating that the increase in DR mainly tends to improve the orientation of the amorphous region in the filaments, 43,44 which would strongly support the mechanical properties of the PET/PTT filaments.…”
Section: Resultsmentioning
confidence: 94%
“…Consequently, electrostatic repulsion arises between the cationic MB molecules and the positively charged active sites on the adsorbent, resulting in The incorporation of chitosan in polycaprolactone (PCL) affects its adsorption capacity. Chitosan has been found to enhance the adsorption capacity of PCL-based materials [41]. A recent study conducted by Martínez and his co-workers indicated that a chitosan-reinforced PCL composite showed adsorption equilibrium capacities for various metal ions, including Zn (II), Cu (II), Fe (II), and Al (III) [42].…”
Section: Effects Of Original Mb Solution Ph and Concentrationmentioning
confidence: 99%
“…The accumulation of solid plastic trash is a significant global issue linked to the traditional usage and disposal of plastic. Accumulations of plastic garbage on land and in the ocean are causing tremendous harm to the ecosystem 1 . Efforts to decrease plastic waste and the resulting pollution of water and land have been ongoing for many years, including the search for alternatives 2 .…”
Section: Introductionmentioning
confidence: 99%